IMPLEMENTASI PELATIHAN MENJAHIT TAS DALAM MENINGKATKAN KEMAMPUAN BERWIRAUSAHA PADA MASYARAKAT DI LKP LITA DESA CIPATIK - Sazidan, Muhamad Nizar; Elsap, Dewi Safitri (IKIP Siliwangi, 2025)
This research is motivated by the economic conditions of the local community. The demographic condition in Village Cipatik indicates that 26.64% of the population is unemployed or has not yet started working, and 26.80% are housewives. The implementation of a bag sewing training program at LKP LITA in Desa Cipatik aims to address the economic issues faced by the community. The theoretical framework used includes the basic concepts of implementation, training, bag sewing, and entrepreneurship. The research method employed is a qualitative approach with a case study method. The respondents involved in this study include five individuals: the head of the program, a tutor, and three community members. Based on the research findings, it was discovered that the implemented program motivates the community to engage in entrepreneurial activities related to bag sewing. The discussion emphasizes that the research aims to enhance the entrepreneurial skills of the community. In conclusion, the bag sewing training program has a positive impact on the community members who aspire to improve their lives.